2021
DOI: 10.1021/acsami.1c03019
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Superhydrophobic Polycaprolactone-Based Composite Membrane with an Alternated Micro–Nano Hierarchical Structure as an Eco-friendly Oil/Water Separator

Abstract: Extraordinary superhydrophobic polycaprolactone (PCL) composite membranes with an alternated hierarchical micro−nano structure were designed by addition of SiO 2 aerogel. The highest water contact angle (WCA) of 166.8 ± 1.5°was obtained when SiO 2 aerogel content was 0.5% (PCL/SiO 2 -a0.5) in the PCL composite membrane, which was higher than other reported polymer-based membranes. SiO 2 aerogel lowered PCL composite membrane's surface energy. The triple curvature structure composed of microspheres, nanospheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Similarly, the characteristic peak observed at 1732 cm -1 which corresponds to C=O, has shifted to a lower value. These results indicated that the PCL has effectively interacted with CA to form a blend (He et al 2021). Similarly, Figure 2c The tensile strength and percentage elongation of the prepared neat and blend membrane are depicted in Figure 2d.…”
Section: Membrane Characterizationmentioning
confidence: 86%
“…Similarly, the characteristic peak observed at 1732 cm -1 which corresponds to C=O, has shifted to a lower value. These results indicated that the PCL has effectively interacted with CA to form a blend (He et al 2021). Similarly, Figure 2c The tensile strength and percentage elongation of the prepared neat and blend membrane are depicted in Figure 2d.…”
Section: Membrane Characterizationmentioning
confidence: 86%
“…To describe the permeation pressure of membrane contacting with oil or water, wetting mechanisms of PVDF and PVDF-P/P-ZIF-TA are illustrated in Figure 12. The permeation pressure was calculated according to the Laplace equation, as shown in the following equation: [14,59] Δp = 2𝜎 L ∕r = −4𝜎 L cos 𝜃∕d (1) whereΔp is the intrusion pressure, 𝜎 L is surface tension of a liquid, r is droplet radius, d is the average pore size of membrane, and 𝜃 is contact angle. PVDF membrane contacting with water will prevent water from passing through membrane pores due to 𝜃>90°and Δp>0, while oil droplets will penetrate PVDF membrane due to𝜃<90°and Δp<0.…”
Section: Oil-in-water Emulsion Separationmentioning
confidence: 99%
“…Filtration oil-water separation treats oily wastewater through size sieving. [14] Oilwater mixtures, including slick oil, dispersed oil, and emulsified oil, can be separated by selecting filter separation materials with different pore sizes. [15] Membrane technology can process oilwater emulsion with high separation efficiency and user-friendly operation, but there is a problem of membrane fouling in the separation process.…”
Section: Introductionmentioning
confidence: 99%
“…Various environmentally friendly polymers were used to fabricate fibrous membranes for oil/water separation, such as cellulose, polylactide (PLA), and polycaprolactone (PCL). Among these, PCL is considered the most potential candidate for making membranes for oil/water separation due to its mechanical property and processing advantages. , In previous studies, PCL has been widely used to develop novel superhydrophobic biodegradable separation materials due to its hydrophobic nature. , However, the separation ability of the superhydrophobic membranes made from PCL is limited because these membranes were mainly used for separating heavy oil/water mixtures and water-in-oil emulsions. Therefore, PCL should be modified to create a superamphiphilic membrane, which could be prewetted to control the separation of different oil/water mixtures, including immiscible oil/water mixtures, oil-in-water emulsions, and water-in-oil emulsions.…”
Section: Introductionmentioning
confidence: 99%